2009
DOI: 10.1179/102453309x439845
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variants and clinical importance ofβ-thalassaemia traits found in the state of Orissa, India

Abstract: Prevention of beta thalassaemia implies knowledge of the molecular spectrum occurring in the population at risk. This knowledge is necessary, especially when a prevention protocol is applied to a multiethnic population. For this purpose, we carried out molecular analysis of 431 beta thalassaemia subjects belonging to tribal (aboriginal) and non-tribal communities of Orissa, a part of peninsular India and found six types of mutation (four previously unreported and two reported). Molecular analysis of beta gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The widespread distribution of the IVSI-5 (G>C) mutation in the sub-continent suggests a relatively ancient origin, especially given its reported high prevalence in indigenous tribal populations in India Nishank et al 2009). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The widespread distribution of the IVSI-5 (G>C) mutation in the sub-continent suggests a relatively ancient origin, especially given its reported high prevalence in indigenous tribal populations in India Nishank et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…The data for Sri Lanka were not geographically subdivided since prolonged civil unrest had resulted in marked under-representation of the Tamil and Muslim minorities in the northern and eastern parts of the country. The data on β-thalassaemia alleles in the population of India were based on the recent comprehensive meta-analysis by Sinha et al (2009) drawn from 17 studies reported between 1991 and 2009, supplemented by additional data from the East Indian state of Orissa (Nishank et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Many studies have described the profile of β thalassaemia mutations in different parts of India. (Varawalla et al , 1991; Garewal et al , 1994; Verma et al , 1997; Agarwal et al , 2000; Vaz et al , 2000; Bandyopadyay et al , 2004; Edison et al , 2008; Sheth et al , 2008; Colah et al , 2009; Munshi et al , 2009; Nishank et al , 2009). However none of these studies have looked at the variations in the distribution of mutations within individual states, which is expected due to the ethnic diversity of the population.…”
mentioning
confidence: 99%
“…Hb Monroe ( HBB :c.92G>C) was first detected among the Gond tribal community of Central India (Zone-2) where the interaction between α and β-globin chain variants has been demonstrated for influencing the disease severity (Gupta et al, 1991). It was earlier found from Northern part of India (Zone-1) including Uttar Pradesh, Haryana, Punjab; Western part (Zone-3) containing Gujarat, Maharastra and Eastern part (Zone-5) counting Orissa (Panigrahi et al, 2007; Nishank et al, 2009; Colah et al, 2010; Nagar et al, 2015; Nigam et al, 2017; Bakhle et al, 2018). A large scale demographic study done in different states of India revealed the overall frequency of this mutation in India is 2.6%.…”
Section: Resultsmentioning
confidence: 93%